Preparation of Reservoir’s Development Program Using SWOT Analysis - Ainur Komariah; Rian Prasetyo; Muhammad Husein; Mathilda Sri Lestari (Universitas Veteran Bangun Nusantara, 2025)
Karangasem Village, Bulu District, Sukoharjo Regency has natural potential in the form of a reservoir that has not been utilized optimally. To develop a reservoir development program, a SWOT analysis was carried out using a focused group discussion method between the Community Service Team from Veteran Bangun Nusantara Sukoharjo University, the Karangasem Village Government, and the GP Fish Farmers Group. The data collection stage produces strength data, namely: it has sufficient area, the depth reaches 1.5 m, the volume of water that can be accommodated reaches 22,500 m3, the condition of the water in the reservoir is considered quite good based on the inflow and outflow of water, the level of water infiltration is not too high. high, has an electricity network, and has an internet network. The weakness is that the location of the embung is far from the city center, Mount Pegat still lacks visitors, the knowledge of the embung managers is still minimal. The opportunity is that fishing activities have many enthusiasts, they can activate social media for promotion. The threat is that it has to compete with other water tourism in the Sukoharjo and Wonogiri areas. From the results of the SWOT analysis, a decision was obtained to develop the embung into a fishing tourist attraction and floating net cages. Keywords: embung, SWOT, fishing, cages